Intervensi Psikososial Terhadap Pasien Di Ruang Rehabilitasi Rumah Sakit Jiwa Naimata [Psychosocial Interventions for Patients in the Rehabilitation Room of Naimata Mental Hospital] - Sariano, Claudia Madyatric; Asbanu, Aprilia Natasya Aurola; Tada, Marike Magi; Tokan, Manggota Alviani Benga; Boling, Deverio Y; Ufi, Ifandry Mega Wati Ndu; Panis, Marleny Purnamasary; Wijaya, Pasfikus Christa (Indonesia Berdaya, 2025)
Abstract. The lack of self-acceptance, low self-esteem, and insufficient social support can lead to inner conflicts both with oneself and with those around, which can hinder the healing process of patients at Naimata Regional Mental Hospital. Psychosocial intervention activities are conducted as support in the healing process of patients in the rehabilitation room of Naimata Regional Mental Hospital. The psychosocial intervention activities utilize a psychoeducation method with three techniques: sharing sessions, art therapy, and forgiveness therapy. Through the psychosocial intervention activities conducted for patients in the rehabilitation room of Naimata Regional Mental Hospital, it was found that the patients actively participated in these activities. The success of the three techniques is measured by the achievement of the goals of each technique applied to the patients, and these techniques are considered successful because each patient participated in the activities and understood them. This understanding was assessed through several questions related to the three techniques: sharing sessions, art therapy, and forgiveness therapy. This process is expected to be useful and beneficial for patients to help enhance inner peace and accelerate the healing process of patients at Naimata Regional Mental Hospital. Abstrak. Kurangnya penerimaan diri, rendahnya harga diri, dan kurangnya dukungan sosial, dapat menjadi konflik batin baik dengan diri sendiri maupun dengan orang di sekitar, yang mana hal ini dapat menghambat proses penyembuhan pasien di Rumah Sakit Daerah Jiwa Naimata. Kegiatan intervensi psikososial yang dilakukan sebagai dukungan dalam proses penyembuhan para pasien di ruang rehabilitasi Rumah Sakit Daerah Jiwa Naimata. Kegiatan intervensi psikososial yang dilakukan menggunakan metode psikoedukasi dengan tiga teknik yang digunakan yakni sharing session, art therapy, dan forgiveness therapy. Melalui kegiatan intervensi psikososial yang dilakukan kepada para pasien di ruang rehabilitasi Rumah Sakit Daerah Jiwa Naimata, didapati hasil bahwa para pasien mengikuti kegiatan ini dengan  berpartisipasi aktif, keberhasilan dari ketiga teknik ini diukur dengan ketercapaian tujuan dari setiap teknik yang diaplikasikan kepada para pasien dan ketiga teknik ini dikatakan mencapai tujuan karena setiap pasien mengikuti kegiatan tersebut dan memahaminya  ini diukur dengan beberapa pertanyaan yang diajukan berkaitan dengan ketiga teknik tersebut yakni sharing session, art therapy, dan forgiveness therapy. Proses ini diharapkan dapat berguna dan bermanfaat bagi para pasien untuk membantu meningkatkan perdamaian dalam diri dan mempercepat proses penyembuhan para pasien di Rumah Sakit Daerah Jiwa Naimata.